Do Studies on Cortical Plasticity Provide a Rationale for Using Non-Invasive Brain Stimulation as a Treatment for Parkinson’s Disease Patients? - Koch, Giacomo (Frontiers in Neurology, 2013)
Animal models of Parkinson’s disease (PD) have shown that key mechanisms of cortical plasticity such as long-term potentiation (LTP) and long-term depression (LTD) can be impaired by the PD pathology. In humans protocols of non-invasive brain stimulation, such as paired associative stimulation (PAS) and theta burst stimulation (TBS), can be used to investigate cortical plasticity of the primary motor cortex. Through the amplitude of the motor evoked potential (MEP) these transcranial magnetic stimulation methods allow to measure both LTP-like and LTD-like mechanisms of cortical plasticity. So far these protocols have reported some controversial findings when tested in PD patients. While various studies described evidence for reduced LTP- and LTD-like plasticity, others showed different results, demonstrating increased LTP-like and normal LTD-like plasticity. Recent evidence provided support to the hypothesis that these different patterns of cortical plasticity likely depend on the stage of the disease and on the concomitant administration of levo-dopa. However, it still unclear how and if these altered mechanisms of cortical plasticity can be taken as a reliable model to build appropriate protocols aimed at treating PD symptoms b